Leading with cultural intelligence : the new secret to success - Livermore, David A., 1967- (American Management Association, 2010)
Why are some leaders able to create trust and negotiate contracts with Chinese, Latin Americans, and Germans all in the same day, while others are barely able to manage the diversity in their own offices? The answer lies in their cultural intelligence, or CQ. Packed with practical tools, research, and case studies, Leading with Cultural Intelligence breaks new ground, offering today's global workforce a specific, four-step model to becoming more adept at managing across cultures.